(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Prior reviews argue that unsafe sexual behaviors and poor HIV knowledge significantly increase the probability of acquiring HIV infections among adolescents. This study assessed the predictors of HIV prevention knowledge and sexual behaviors among Makerere university students in Uganda. Methods: We performed a cross-sectional survey. We performed a normality test using Shapiro Wilk test on knowledge score. Results revealed that knowledge score was not normally distributed. The study used two sample Wilcoxon Rank Sum and Kruskal Wallis Rank tests to assess the effect of HIV knowledge on demographic characteristics and sexual behaviors. Post-hoc tests were conducted using Bonferroni correction. Spearman rank correlation test was used for continuous variables while Chi-square and Fisher’s tests were used for categorical variables to assess the relationship between demographic characteristics and sexual behaviors. Results: We report results for 1337 students. The mean age was 21.2SD (1.6) and more than half 700(52.4%) were male students. The median HIV prevention knowledge score of students was 13 IQR (11-15) in the range of 0 to 18. Males significantly scored higher than females (13.0 IQR (12-15) vs. 12.0 IQR (10-14) p=0.000), an increase in age was associated with higher knowledge scores (Rho = 0.101, p = 0.000). Students in the third year of study significantly scored higher than those in the first year, and government-sponsored students scored higher than the privately sponsored students. HIV knowledge was also significantly associated with sexual experience, and condom use at univariate level but insignificant at multiple level analysis. Males were more likely to have ever had sex (31.7% vs. 12.7%) and ever used a condom (63% vs. 55%) than females respectively Conclusion: Our findings suggest that Makerere University students possessed good knowledge on HIV. There is evidence of an association between student’s knowledge, and demographic characteristics and a few sexual behaviors. Future behavioral and educational programs that target both sexually and non-sexually experienced students should address the gender differences.